Impact of the "atherosclerotic pabulum" on in‐hospital mortality for SARS‐CoV‐2 infection. Is calcium score able to identify at‐risk patients?. Issue 6 (30th March 2022) - Pergola, Valeria; Cabrelle, Giulio; Previtero, Marco; Fiorencis, Andrea; Lorenzoni, Giulia; Dellino, Carlo Maria; Montonati, Carolina; Continisio, Saverio; Masetto, Elisa; Mele, Donato; Perazzolo Marra, Martina; Giraudo, Chiara; et al.
Abstract: Background: Although the primary cause of death in COVID‐19 infection is respiratory failure, there is evidence that cardiac manifestations may contribute to overall mortality and can even be the primary cause of death. More importantly, it is recognized that COVID‐19 is associated with a high incidence of thrombotic complications. Hypothesis: Evaluate if the coronary artery calcium (CAC) score was useful to predict in‐hospital (in‐H) mortality in patients with COVID‐19. Secondary end‐points were needed for mechanical ventilation and intensive care unit admission. Methods: Two‐hundred eighty‐four patients (63, 25 years, 67% male) with proven severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection who had a noncontrast chest computed tomography were analyzed for CAC score. Clinical and radiological data were retrieved. Results: Patients with CAC had a higher inflammatory burden at admission (d ‐dimer, p  = .002; C‐reactive protein, p  = .002; procalcitonin, p  = .016) and a higher high‐sensitive cardiac troponin I (HScTnI, p  = <.001) at admission and at peak. While there was no association with presence of lung consolidation and ground‐glass opacities, patients with CAC had higher incidence of bilateral infiltration ( p  = .043) and higher in‐H mortality ( p  = .048). On the other side, peak HScTnI >200 ng/dl was a better determinant of all outcomes in both univariate ( p  = <.001) and multivariate analysis ( p  = <.001). Conclusion: The main finding of our research is that CAC was positively related to in‐H mortality, but it did not completely identify all the population at risk of events in the setting of COVID‐19 patients. This raises the possibility that other factors, including the presence of soft, unstable plaques, may have a role in adverse outcomes in SARS‐CoV‐2 infection.